2021
DOI: 10.5812/aapm.112830
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Hypotension Increased Risk in the Oncological Patient

Abstract: : Patient safety advocacy involves avoiding, preventing, and amelioration of adverse outcomes or injuries caused by the process of healthcare rather than a patient's underlying medical illness. Intraoperative hypotension (IOH), a common morbid event, reduces perfusion to critical organs and tissues and has a wide incidence, depending on how it is defined. IOH has adverse intraoperative and postoperative consequences, which make its prevention important to improve patient outcomes. Certain populations have even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…Moreover, the burden of cardiovascular risk factors and their prevalence increased over time [27]. In particular, cancer surgeries can be prolonged and procedurally complicated, carrying an increased risk of the procedure itself, such as significant blood loss, deep vein thrombosis, pressure sores, and respiratory or cardiovascular instability [28].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the burden of cardiovascular risk factors and their prevalence increased over time [27]. In particular, cancer surgeries can be prolonged and procedurally complicated, carrying an increased risk of the procedure itself, such as significant blood loss, deep vein thrombosis, pressure sores, and respiratory or cardiovascular instability [28].…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining lower blood pressure is linked to reduced blood loss and a clearer surgical field. Controlled hypotension, commonly defined as a 30% decrease in MAP, may vary due to reported cases of organ failure, including acute kidney injury, myocardial injury, and mortality during the procedure [35][36][37][38]. Zamani et al found that while both sedatives decreased bleeding during surgery, patients who received remifentanil experienced more pronounced outcomes [11].…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative low cardiac output and hypotension disrupt perfusion to the kidney that potentially causes graft failure, as well as maintaining perfusion within normal autoregulation, decrease the risk of organ complications in high-risk cardiac and non-cardiac surgical patients ( 22 , 23 ). In perioperative and intensive care medicine, static parameters such as central venous pressure (CVP) or mean arterial blood pressure (MAP) have limitations as hemodynamic monitoring in high-risk surgical patients ( 24 ).…”
Section: Discussionmentioning
confidence: 99%